2015
DOI: 10.1155/2015/481245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Left Ventricular Outflow Tract Obstruction on Left Atrial Mechanics in Hypertrophic Cardiomyopathy

Abstract: Left atrial (LA) volumes are known to be increased in hypertrophic cardiomyopathy (HCM) and are a predictor of adverse outcome. In addition, LA function is impaired and is presumed to be due to left ventricular (LV) diastolic dysfunction as a result of hypertrophy and myocardial fibrosis. In the current study, we assess the incremental effect of outflow tract obstruction (and concomitant mitral regurgitation) on LA function as assessed by LA strain. Patients with HCM (50 obstructive, 50 nonobstructive) were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 20 publications
2
30
0
3
Order By: Relevance
“…Our findings, consistent with those of previous studies, have shown that septal myectomy in patients with HCM results in a decrease in all LA volumes. 7,8,11,12 We have shown that following surgical myectomy LA active myectomy was similar to patients with no intra-ventricular conduction abnormalities 38 . Indeed, LVOT gradient has been shown to be associated with E/e′ lateral ratio and tissue Doppler of the mitral annulus early diastolic velocity.…”
Section: Predictors Of Reduction Of Maximal La Volume After Myectomymentioning
confidence: 89%
See 3 more Smart Citations
“…Our findings, consistent with those of previous studies, have shown that septal myectomy in patients with HCM results in a decrease in all LA volumes. 7,8,11,12 We have shown that following surgical myectomy LA active myectomy was similar to patients with no intra-ventricular conduction abnormalities 38 . Indeed, LVOT gradient has been shown to be associated with E/e′ lateral ratio and tissue Doppler of the mitral annulus early diastolic velocity.…”
Section: Predictors Of Reduction Of Maximal La Volume After Myectomymentioning
confidence: 89%
“…Several studies have documented increased LA volumes in HCM patients. 7,8,12 The LA appears to initially increase its volume by stretching to compensate for the increased loading conditions resulting from significant LVOTO, mitral regurgitation and diastolic dysfunction while maintaining normal compliance. It is plausible that as LA enlargement increases beyond the Frank-Starling relationship, it results in a significant reduction in the atrial booster pump function, which again results in reduced LA emptying fraction.…”
Section: Predictors Of Reduction Of Maximal La Volume After Myectomymentioning
confidence: 99%
See 2 more Smart Citations
“…LVOTO and mitral regurgitation further impair left atrium mechanics [11]. In HCM, the left atrium is often enlarged and its size provides important prognostic information [12].…”
Section: Key Pointsmentioning
confidence: 99%